2022
DOI: 10.1111/bju.15758
|View full text |Cite
|
Sign up to set email alerts
|

LEARN: a multicentre, cross‐sectional evaluation of Urology teaching in UK medical schools

Abstract: To evaluate the status of UK undergraduate urology teaching against the British Association of Urological Surgeons (BAUS) Undergraduate Syllabus for Urology. Secondary objectives included evaluating the type and quantity of teaching provided, the reported performance rate of General Medical Council (GMC)-mandated urological procedures, and the proportion of undergraduates considering urology as a career. Subjects and MethodsThe uroLogical tEAching in bRitish medical schools Nationally (LEARN) study was a natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 35–37 Moreover, a UK medical education report determined that ED is one of the least-taught topics in medical schools, with 43.8% coverage, potentially explaining gaps in knowledge, skills, and attitudes regarding its prevention and proper management. 38 Coupled with the fact that ED is correlated with reduced physical-emotional satisfaction and can be linked to poor quality of life, depression, and lack of adherence to specific treatments, 33 there is an urgent need to implement health guidance and monitoring programs in vital environments such as universities. Such initiatives could significantly influence medical training and education.…”
Section: Discussionmentioning
confidence: 99%
“… 35–37 Moreover, a UK medical education report determined that ED is one of the least-taught topics in medical schools, with 43.8% coverage, potentially explaining gaps in knowledge, skills, and attitudes regarding its prevention and proper management. 38 Coupled with the fact that ED is correlated with reduced physical-emotional satisfaction and can be linked to poor quality of life, depression, and lack of adherence to specific treatments, 33 there is an urgent need to implement health guidance and monitoring programs in vital environments such as universities. Such initiatives could significantly influence medical training and education.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a multicenter, cross-sectional evaluation of urology teaching in the UK showed that 20.1% of foundation year 1 doctors received no medical school attachment in urology prior to working on the hospital ward. 16 The results indicate urology teaching can vary considerably in the UK, which prompts speculation of inadequate “lobbying power” within our current medical school curriculum. These are a few challenges that may prevent the advancement of medical school urological teaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, little has been reported on medical students' exposure and teaching methods regarding plastic surgery. Indeed, plastic surgery teaching has lagged behind other major surgical specialties (such as urology, which is compulsory in 76% of medical schools in Europe 3 ), with some medical schools not including any plastic surgery teaching. The hypotheses for this are variable: some state that the medical school curriculum is already too intense to include plastic surgery in the curriculum, 4 while others feel that greater focus is being given toward preparing more general practitioners (GPs).…”
Section: Introductionmentioning
confidence: 99%